Penggunaan Telemonitoring untuk Mengurangi Readmisi pada Pasien Gagal Jantung - Kapriana Tanty Natalia; Denissa Faradita Aryani; Tuti Herawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effectiveness of telemonitoring on the incidence of readmission in patients with heart failure. The method used in this study is a literature review focusing on articles published in the last five years and English, with the target population being patients aged over 18 years. The article search strategy uses online databases, namely